PERHITUNGAN NILAI NOISE APLIKASI SOFTWARE IMAGEJ DENGAN VARIASI PIXEL SIZE MENGGUNAKAN FOV 375, FOV 395, FOV 415 DENGAN MATRIX SIZE SAMA PADA PEMERIKSAAN CT SCAN ABDOMEN - MUHAMMAD RAIZA RAFINDI; YUKI MULYANI (Poltekes Bhakti Pertiwi Husada, 2023)
FOV( Field of View ) is the diameter of the maximum and the picture which will be reconstructed. Has been conducted research program application the use of field of fiew for reckoning the pixels size against noise on CT scans the abdomen is. The aim of this research is to find out the influence of the variation of pixels size by using FOV 373, 395, and 415 with the same matrix size against noise on CT scans the abdomen is. A kind of this research deskriftif with the approach of quantitative. The study is done in the department of radiologist RSUD Indramayu. To obtain data in this research, the use writers a method of collecting data by means of observations directly with comparing workup CT scans the abdomen with 3 times comparing variation FOV. After that, the result is taken from a snippet axial the same against samples. Several pictures be judged by imageJ and counted the use of tabulating with the formula noise, and the result analysis meggunakan the result of calculating standard deviations from noise on 3 variation FOV used in descriftive. The results showed an increase in the value of the results of the use of noise variation pixel size by using the FOV 375, 395, and 495 with matrix of the same size of the noise on a CT Scan of the abdomen that is for FOV 375 with an average of 8.98 and std. deviation of 0.89, FOV 395 with an average of 9.84 and std. deviation 1.63, and to the FOV 415 with an average 10.86 and std. deviation of 2.31.